Seeking Out the Land - Safrai, Zeʾev (Jewish and Christian Perspectives Ser, 2018)
Intro -- Contents -- Editorial Statement -- Acknowledgements -- List of Illustrations -- Abbreviations -- Introduction -- The Purpose of the Book -- The Approach of the Ancients to the Bible -- Chapter 1 The Geography of the Land in Second Temple Literature -- 1.1 Apocrypha and Pseudepigrapha -- 1.1.1 The Land as Backdrop of the Narrative -- 1.1.2 Praises of the Land: The Letter of Aristeas -- 1.1.3 Descriptions of Biblical Events -- 1.1.4 Extrabiblical Narratives -- 1.1.5 Fictitious Geography -- 1.2 Greek Jewish Writers from Egypt -- 1.2.1 Philo -- 1.2.2 Eupolemus, Theodotus -- 1.3 The Septuagint -- 1.4 The Essene Writings -- 1.4.1 The Attitude toward the Land -- 1.4.2 Actual Information on the Land -- Chapter 2 The Description of the Land of Israel in Josephus' Works -- 2.1 The Description of the Land of Israel (War 3:35-58) -- 2.1.1 Sources -- 2.1.2 Additions -- 2.1.2.1 The Description of Samaria -- 2.1.2.2 Idumaea -- 2.1.2.3 Coastal Region -- 2.1.2.4 Administrative Division -- 2.1.2.5 Agrippa's Kingdom -- 2.2 Jericho and Gennesar (War 3:506-521, 4:451-476) -- 2.3 Jerusalem, Jotapata, Gamala, Machaerus, and Masada -- 2.4 Biblical Geography in Josephus -- 2.5 The Portions of the Tribes -- 2.6 Scattered Descriptions -- 2.6.1 Identifications -- 2.6.2 Additions -- 2.6.3 Anachronistic Terminology -- 2.7 Conclusions -- Chapter 3 The Land in Rabbinic Literature -- 3.1 The Land-Dependent Commandments -- 3.1.1 Halakha and Sanctity -- 3.1.2 The 'Impurity of Non-Jewish Lands' -- 3.1.3 The Land-Dependent Commandments -- 3.1.3.1 The 'Canonical' Halakhic Rule -- 3.1.3.2 The Land-Dependent Commandments in Second Temple Literature -- 3.1.3.3 Josephus -- 3.1.3.4 Sectarian Literature -- 3.1.3.5 Rabbinic Sources - First Century -- 3.1.3.6 Land-Dependent Commandments in Rabbinic Literature - The Basic Explanation